2D MoS2 nanosheets on 1D anodic TiO2 nanotube layers: an efficient co-catalyst for liquid and gas phase photocatalysis. Issue 48 (3rd December 2019) - Motola, Martin; Baudys, Michal; Zazpe, Raul; Krbal, Miloš; Michalička, Jan; Rodriguez-Pereira, Jhonatan; Pavliňák, David; Přikryl, Jan; Hromádko, Luděk; Sopha, Hanna; Krýsa, Josef; Macak, Jan M.
Abstract : A novel 1D nanotubular TiO2 /MoS2 nanosheet heterostructure possesses synergistic effects that yield superior photon-to-electron conversion and photocatalysis. Abstract : One-dimensional TiO2 nanotube layers with different dimensions were homogeneously decorated with 2D MoS2 nanosheets via atomic layer deposition and employed for liquid and gas phase photocatalysis. The 2D MoS2 nanosheets revealed a high amount of exposed active edge sites and strongly enhanced the photocatalytic performance of TiO2 nanotube layers.